THE ROLE OF RESILIENCE ON MOTIVATION AMONG BRAZILIAN ATHLETICS AND SWIMMING PARATHLETES - José Roberto Andrade do Nascimento Junior; Gabriel Lucas Morais Freire; Carla Thamires Laranjeira Granja; Natanael Pereira Barros; Daniel Vicentini de Oliveira; Leonardo Gasques Trevisan Costa (Journal of Physical Education)
ABSTRACT This cross-secctional study investigated the role of resilience on motivation among athletics and swimming parathletes. The subjects were 64 male (n=41) and female (n=23) parathletes from North and Northeast regions of Brazil. The parathletes were practitioners of athletics (69.5%) and swimming (30.5%), with mean age of 28.42±11.32 years. The instruments were the Sport Motivation Scale-II and Connor-Davidson Resilience Scale. Data analysis was conducted thorugh Kolmogorov Smirnov, Spearman correlation and Path Analysis (p<0.05). The results showed that resilience showed significant correlation (p<0.05) with all controlled and autonomous regulations: external (r=0.29), introjected (r=0.40), identified (r=0.29), integrated (r=0.26) and intrinsic (r=0.42). Path Analysis revealed that that resilience showed a significant (p 0.05) and effect on intrinsic, introjected and external regulations, explaining 16%, 11% and 11% of the variance of the variables, respectively. It should be noted that resilience had a moderate and positive effect on intrinsic (β=0.40), introjected (β=0.33) and external (β=0.33) regulations. It was concluded that in the context of the paralympic athletics and swimming, resilience seems to be an intervening factor on both autonomous and controlled motivation.